Teasing and claims to non-serious intent in Chinese talk shows. (16th June 2021) - Chang, Wei-Lin Melody; Haugh, Michael
Abstract : While teasing can sometimes cause offence, the limits of what counts as acceptable teasing is a function of the localised sequential environment and broader socio cultural context in which it occurs. In this article, we examine the sequential and moral implications of claims to non-serious intent in teasing sequences arising in television talk shows. Drawing from an analysis of over 28 hours of variety shows broadcast in Mainland China and Taiwan, we examined 25 sequences involving claims by participants to be 'kidding' (kaiwanxiao). From this analysis it emerged that claims to be 'kidding' are used in these contexts to: (1) disclaim any (potential) offence caused through teasing, (2) signal a return to serious talk following teasing, (3) reproach the other for teasing that is construed as going too far, (4) and boost the humorous impact of self-boasting in response to teasing. While the first two are consistent with the usage of equivalent expressions in other languages, the latter two have not been identified in studies to date, thereby underscoring the importance of studying jocular forms of teasing in different linguistic and sociocultural contexts.